Synthesis Methods of Two-Dimensional MoS2: A Brief Review - Jie Sun; Xuejian Li; Weiling Guo; Miao Zhao; Xing Fan; Yibo Dong; Chen Xu; Jun Deng; Yifeng Fu (Crystals, 2017)
Molybdenum disulfide (MoS2) is one of the most important two-dimensional materials after graphene. Monolayer MoS2 has a direct bandgap (1.9 eV) and is potentially suitable for post-silicon electronics. Among all atomically thin semiconductors, MoS2’s synthesis techniques are more developed. Here, we review the recent developments in the synthesis of hexagonal MoS2, where they are categorized into top-down and bottom-up approaches. Micromechanical exfoliation is convenient for beginners and basic research. Liquid phase exfoliation and solutions for chemical processes are cheap and suitable for large-scale production; yielding materials mostly in powders with different shapes, sizes and layer numbers. MoS2 films on a substrate targeting high-end nanoelectronic applications can be produced by chemical vapor deposition, compatible with the semiconductor industry. Usually, metal catalysts are unnecessary. Unlike graphene, the transfer of atomic layers is omitted. We especially emphasize the recent advances in metalorganic chemical vapor deposition and atomic layer deposition, where gaseous precursors are used. These processes grow MoS2 with the smallest building-blocks, naturally promising higher quality and controllability. Most likely, this will be an important direction in the field. Nevertheless, today none of those methods reproducibly produces MoS2 with competitive quality. There is a long way to go for MoS2 in real-life electronic device applications.